Race, Ethnicity and Global Communication Studies - Kraidy, Marwan M (2007)
Race, as Downing and Husband (2005) remind us, is a ‘social category’ without a ‘scientific basis’ (p. 2). And yet, for better or worse, race is a fundamental dimension of contemporary life, one of the few master tropes that define identities, elicit solidarities and operate as an instrument of othering. Though ‘more inclusive and less objectifying’ (Spencer, p. 45), ethnicity is a ‘transient concept’ (p. 47) that, perhaps more so than ‘race’, reflects public and scholarly understandings of difference. They can also be burning issues in the life of nations and regions. As I am writing these words, public discourse in the United States has for several weeks been agitated by radio talk-show Don Imus’s racist comments about the Rutgers University women’s basketball team, the French intelligentsia is enjoying a collective sigh of relief at the weaker-than expected performance in the 2007 presidential election of the far-right and xenophobic French politician Jean-Marie Le Pen, and sectarian polarization between Sunnis and Shi’as is gripping the Arab world, fuelled by the botched US–British occupation of Iraq, rhetorical war between the US and Iran and the consequences of the Israel–Hizbullah war in Lebanon in the summer of 2006